STUDY OF ONLINE SINGLE SUBMISSION-BASED INTEGRATED SERVICE IMPLEMENTATION IN BANYUWANGI DISTRICT - Nadya Ayu Putri Hidayat; Hary Priyanto; Erna Agustina (RADJA PUBLIKA, 2023)
The provision of services to the community in a dignified and easy manner is the aim of the Government of Banyuwangi Regency in its policy regarding public service delivery policies. Online single submission (OSS) is an acceleration and convenience mechanism so that there is no room for bureaucrats not to take advantage of community service activities. The implementation of ideal services is a sign that public services must meet the needs of the community regarding goods, services, and administration. Objectives: To describe, analyze, and interpret integrated services based on online single submission in Banyuwang Regency. Method: Using a qualitative approach based on a constructive and participatory scheme. The existence of primary data obtained from the acquisition of interviews, while the existence of secondary data obtained from literature and various regulations relevant to the research topic. Results: OSS-based services as an implementation of e-government services are not in the context of eliminating conventional model services, because the nature of public services is human activity. Conclusion: OSS-based services aim to accelerate and open up services so as to trim away the reality of pathology in the delivery of public services.